2020
DOI: 10.1021/acsami.0c05735
|View full text |Cite
|
Sign up to set email alerts
|

Optical Thermometry with Quantum Emitters in Hexagonal Boron Nitride

Abstract: Nanoscale optical thermometry is a promising non-contact route for measuring local temperature with both high sensitivity and spatial resolution. In this work, we present a deterministic optical thermometry technique based on quantum emitters in nanoscale hexagonal boron-nitride. We show that these nanothermometers exhibit better performance than that of homologous, all-optical nanothermometers both in sensitivity and range of working temperature. We demonstrate their effectiveness as nanothermometers by monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Most recently, hexagonal boron nitride (hBN)-a wide-band-gap (∼6 eV) two-dimensional (2D) semiconductor with some excellent properties-has emerged as an alternative pathway for integrated nanophotonics [19]. There has been a lot of studies on single-photon emitters (SPEs) in hBN [20][21][22][23][24][25][26][27][28][29], because of the extreme brightness [25,28], photoluminescence (PL) stability [21,28], and large stark-shift tuning [23,26]. In addition, some defects display spin-optical quantum properties and can be initialized, manipulated and optically read out at room temperature [30][31][32][33], showing the potential of this material system.…”
mentioning
confidence: 99%
“…Most recently, hexagonal boron nitride (hBN)-a wide-band-gap (∼6 eV) two-dimensional (2D) semiconductor with some excellent properties-has emerged as an alternative pathway for integrated nanophotonics [19]. There has been a lot of studies on single-photon emitters (SPEs) in hBN [20][21][22][23][24][25][26][27][28][29], because of the extreme brightness [25,28], photoluminescence (PL) stability [21,28], and large stark-shift tuning [23,26]. In addition, some defects display spin-optical quantum properties and can be initialized, manipulated and optically read out at room temperature [30][31][32][33], showing the potential of this material system.…”
mentioning
confidence: 99%
“…It also allows for the accurate placement of individual nanoprobe with respect to target areas or objects. This was demonstrated in a study that used a fluorescent hBN nanoparticle as an optical nanothermometer-placed deterministically onto a micro-circuit-to measure local temperature and potential hot spots in target areas of the device [175].…”
Section: Beyond Optical Imagingmentioning
confidence: 99%
“…The resulting methacrylated PGLyD was then precipitated in isopropanol (purity: 99.9%, Sigma-Aldrich) and dried under reduced pressure at room temperature (25 ºC) overnight. 1 H-NMR spectra (Bruker ARX 300 MHz, DMSO-d 6 ) suggested that only one methacrylic group was incorporated into PGLyD structure.…”
Section: Coho:pglyd Synthesismentioning
confidence: 99%
“…The number of materials for OPT techniques is remarkably large including organic dyes 3 , semiconductors 4 , synthetic diamonds 5 , quantum emitters 6 and lanthanide complexes 7 . However, the major drawbacks that limit applications of these materials in OPT are the need of ultraviolet/visible/ near-infrared excitations, sophisticated spectrophotometry instrumentation, toxicity and a potentially unstable balance of demand and supply of raw material for the manufacture of OPT devices 8,9 .…”
Section: Introductionmentioning
confidence: 99%